Foreign Policy of Contemporary Poland in the Light of Institutional and Legal Conditions (Economic and Political Thought, 2013)
The article is aimed at analyzing legal and institutional conditions ofcontemporary Polish foreign policy. The contents were divided into fourparts. After the introduction, the author analyzes the institutions responsiblefor the development and implementation of Polish foreign policy. The thirdpart deals with the essence of the Polish foreign policy in the conditions ofcohabitation. In the conclusions, the author points out that the institutionalproblems existing in the Polish foreign policy result from both inaccurateregulations in the 1997 Constitution of the Republic of Poland and personaland political features of the most important people in the state.